2022
DOI: 10.1186/s12889-022-14329-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the role of sleep quality, functional limitation and depressive symptoms in determining life satisfaction among the older Population in India: a moderated mediation approach

Abstract: Background: Life satisfaction (LS), a useful construct in the study of psycho-social well-being, is an important indicator of healthy aging. With a view to investigate whether the improved longevity in India is accompanied by commensurate levels of well-being and contentment among the older adults , this study aimed to examine (1) the association between LS and sleep quality among older Indian adults aged 60 years and above (2) the mediating role of depression that accounts for the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 79 publications
1
12
0
Order By: Relevance
“…Elderly people in NHs reported higher mean PSQI scores than those in the community [ 27 , 28 ], indicating have poor sleep quality. In our study, poor sleep quality was negatively associated with life satisfaction, in line with previous studies [ 61 ], Sleep was a crucial restorative behavior that affects individual health and subjective well-being [ 62 ]. Sleep quality was closely related to some major psychological behaviors, including emotion regulation and interpersonal communication [ 63 , 64 ].…”
Section: Discussionsupporting
confidence: 91%
“…Elderly people in NHs reported higher mean PSQI scores than those in the community [ 27 , 28 ], indicating have poor sleep quality. In our study, poor sleep quality was negatively associated with life satisfaction, in line with previous studies [ 61 ], Sleep was a crucial restorative behavior that affects individual health and subjective well-being [ 62 ]. Sleep quality was closely related to some major psychological behaviors, including emotion regulation and interpersonal communication [ 63 , 64 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we considered depression status as a psychometric factor. LASI embraced the definition of depression as the experience of low mood and no pleasure in performing an activity that was earlier interesting for an extended period, i.e., at least for two weeks [ 48 ]. For the assessment of depression status, the Centre for Epidemiologic Studies Depression (CES-D) scale was used [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies hint that older adults become more susceptible to sleep disorders, which is independently and strongly associated with the deterioration of subjective wellbeing [ 33 ]. In general, various studies concerning the relationship between sleep quality and wellbeing/happiness have shown that low sleep quality is associated with worse health and wellbeing [ 30 ] and the same association is found among the older adults population [ 10 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several demographic variables are found to have confound with the relationships between subjective health, mental feelings, sleep duration and quality, and happiness. These factors include age [ 33 ], gender [ 10 , 35 , 36 ], marital status [ 37 , 38 ], and education [ 34 ]. In general, most of the applied research yielded similar results on the influence of those bio-variables on older adults.…”
Section: Introductionmentioning
confidence: 99%